Norovirus in symptomatic and asymptomatic individuals: cytokines and viral shedding. (25th February 2016) - Newman, K L; Moe, C L; Kirby, A E; Flanders, W D; Parkos, C A; Leon, J S
Summary: Noroviruses (NoV) are the most common cause of epidemic gastroenteritis world-wide. NoV infections are often asymptomatic, although individuals still shed large amounts of NoV in their stool. Understanding the differences between asymptomatic and symptomatic individuals would help in elucidating mechanisms of NoV pathogenesis. Our goal was to compare the serum cytokine responses and faecal viral RNA titres of asymptomatic and symptomatic NoV-infected individuals. We tested serum samples from infected subjects ( n = 26; 19 symptomatic, seven asymptomatic) from two human challenge studies of GI.1 NoV for 16 cytokines. Samples from prechallenge and days 1-4 post-challenge were tested for these cytokines. Cytokine levels were compared to stool NoV RNA titres quantified previously by reverse transcription–polymerase chain reaction (RT–qPCR). While both symptomatic and asymptomatic groups had similar patterns of cytokine responses, the symptomatic group generally exhibited a greater elevation of T helper type 1 (Th1) and Th2 cytokines and IL-8 post-challenge compared to the asymptomatic group (all P < 0·01). Daily viral RNA titre was associated positively with daily IL-6 concentration and negatively with daily IL-12p40 concentration (all P < 0·05). Symptoms were not associated significantly with daily viral RNA titre, duration of viral shedding or cumulative shedding. Symptomatic individuals, compared to asymptomatic, have greater immune system activation, as measured by serum cytokines, but they do not have greater viral burden, as measured by titre and shedding, suggesting that symptoms may be immune-mediated in NoV infection.